Fusion protein strategies for cryo-EM study of G protein-coupled receptors - Zhang, Kaihua; Wu, Hao; Hoppe, Nicholas; Manglik, Aashish; Cheng, Yifan (Nature communications, 2022)
Single particle cryogenic-electron microscopy (cryo-EM) is used extensively to determine structures of activated G protein-coupled receptors (GPCRs) in complex with G proteins or arrestins. However, applying it to GPCRs without signaling proteins remains challenging because most receptors lack structural features in their soluble domains to facilitate image alignment. In GPCR crystallography, inserting a fusion protein between transmembrane helices 5 and 6 is a highly successful strategy for crystallization. Although a similar strategy has the potential to broadly facilitate cryo-EM structure determination of GPCRs alone without signaling protein, the critical determinants that make this approach successful are not yet clear. Here, we address this shortcoming by exploring different fusion protein designs, which lead to structures of antagonist bound A 2A adenosine receptor at 3.4 Å resolution and unliganded Smoothened at 3.7 Å resolution. The fusion strategies explored here are likely applicable to cryo-EM interrogation of other GPCRs and small integral membrane proteins. Here, Zhang et al. explore fusion protein strategies to facilitate cryo-EM structural studies of GPCRs alone- without signal transducers- in ligand bound or unliganded form.